Post-metaphysical Thinking: A Habermasian Perspective on the Critique of Traditional Metaphysics - Seran, Alexander (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
Immanuel Kant has been considered as one of the prominent philosophers that in a way put an end to metaphysics. Kant’s critique of metaphysics is directed towards the totalizing unity of mythological narratives, religious doctrines, and philosophical explanations. The basic concepts of narratives, religions, and philosophy had riled upon a syndrome of validity that dissolved with the emergence of expert cultures in science, morality, and law and with the autonomy of art. Today, philosophy could establish its own distinct criteria of validity under conditions of rationality in relation to science that is fallible. Habermas puts forward that philosophy after Kant can no longer be a metaphysics in the sense of “conclusive” and “totalizing” thinking. In his communication theory, Habermas develops a theory of philosophy that is not reducible to a simple totality but has social complexity as its ground that is a number of plural language games, different orders of power, different structures of politics constituting modern time. Habermas is thus concerned with developing a theory of philosophy in general as a discourse of social differentiation. Keywords:*paradigm shift *metaphysics *post-metaphysics *identity/totalizing thinking *situating reason *proceduralrationality *discourse ethics